Achieving ultra-high hardness of Ti–3Si-1.5Fe–1Mo alloy via tailoring the in-situ Ti5Si3. (January 2023) - Yuan, Jingjiu; Fan, Qunbo; Xu, Shun; Zhang, Hongmei; Yang, Lin; Cheng, Xingwang; Wang, Duoduo; Chen, Kai; Zhou, Yu; Cai, Cheng; Zhou, Siyuan
Abstract: In this work, ultra-high hardness of 598 HV of Ti–3Si-1.5Fe–1Mo alloy was manufactured via tailoring the in-situ Ti5 Si3 phases. The manipulation of solution and precipitation as well as the regulation of morphology and distribution of the in-situ Ti5 Si3 phases were achieved by solution heat treatment and subsequent aging. The average size of Ti5 Si3 in titanium alloy was reduced from 3.13 μm to 2.39 μm, and the tiny Ti5 Si3 was dispersed in the grain interior, while the residual rod-like and particle Ti5 Si3 were distributed at the grain boundaries. The hardness and ultimate compressive strength of the alloys were remarkably increased by 151 HV and 373 MPa, respectively. The improvement of mechanical properties by Ti5 Si3 evolution was mainly ascribed to the unique regulation of morphology and distribution of Ti5 Si3 and Si-involved variation in solute. Moreover, the degree of solid solution strengthening of Si element produced by the evolution of Ti5 Si3 was quantitatively obtained by theoretical calculation of phase diagram. Highlights: Ultra-high hardness (598 HV) of Ti–3Si-1.5Fe–1Mo alloy is achieved. The solid solubility of Si is elaborately controlled based on the phase diagram. The intra-grain dispersion of tiny Ti5 Si3 precipitates is tailored by aging treatment. Effect of Ti5 Si3 evolution on the mechanical properties is quantitatively revealed.